Scientific Questions of Fact Between Free Evaluation of Evidence and Proof Beyond any Reasonable Doubt in the Criminal Trial - Gaetano Carlizzi (Quaestio Facti)
In contemporary legal epistemology it is common to talk about the “paradox of expert testimony”, which can be formulated as follows: “how can the judge assess information provided by an expert witness if he needs him precisely because of his own lack of adequate specialist knowledge?”. The goal of the paper is to show that this paradox is only apparent. To pursue it I first of all review the history of the ideas of free evaluation of evidence and proof beyond any reasonable doubt in the civil law and common law traditions, in order to address the theoretical problem of their nature in contemporary law systems. Then I propose a taxonomy of the judicial approaches to the role of experts at trial, concluding that none of these approaches, except one (“the gatekeeper judge”), is consistent with both above-mentioned principles. Lastly, I look in depth at the gatekeeper judge approach, showing that a real assessment of expert information is possible, so that the paradox of expert testimony depends only on a faulty understanding of both activities.